Criteria for high-performance medicines' management in hospitals†. Issue 2 (12th March 2012) - Söderlund, L.A.; Eriksson, T.; Alenius, M.
Abstract : Background: Chronic kidney disease (CKD) is currently an important complication of HIV infection once HAART treatment has been introduced. Purpose: The aim of this study was to investigate the prevalence of CKD and patient characteristics in HIV-infected patients. Materials and methods: This was a retrospective cross-sectional study. In May 2011, using a cross-sectional method, the authors selected all HIV patients receiving antiretroviral treatment at a tertiary university hospital in Spain. The medical charts were reviewed from the moment the HAART treatment was started. Exclusion criteria included those who did not follow the treatment throughout the study period and those who were on treatment less than 6 months. The following demographic, clinical and laboratory parameters were abstracted from the clinical database: age, nadir CD4 T cell count, viral load, estimated glomerular filtration rates (GFR), hepatitis B and C co-infection, medicines, hypertension, diabetes mellitus and other co-morbidities. GFR was ascertained according to the Modification of Diet in Renal Disease (MDRD-4) criteria. CKD was defined as GFR <60 ml/min for at least 3 months. Results: During the study period 149 patients needed antiretroviral treatment at the HIV consulting service. CKD prevalence was 7.38% (11 patients). The patients' characteristics were: CKD (n=11) No CKD (n=133) p-value age (mean (SD)) 45 (9.1) 44.9(8.0) 0.92 male gender (n(%)) 8 (72.7) 99 (74.4) 0.81 homosexual 1 (9) 33 (24.8) IDU 8 (72.7) 58 (43.6) 0.06 heterosexual 2 (18.2) 43 (32.3) HCV infection (n(%)) 8 (72.7) 51 (38.3) 0.04 HCV-HBV co-infection (n(%)) 1 (9) 3 (2.2) Nadir CD T cells (median) 358.70 355.25 undetectable viral load (n(%)) 11(100) 118 (88.7) 0.35 tenofovir (TFV) exposure 6 (54.5) 83 (63.4) 0.78 lamivudine exposure 5 (45.4) 15 (11.2) <0.005 Hypertension 3 (27.3) 15 (11.3) 0.31 diabetes 1 (9) 3 (2.2). Conclusions: The prevalence of CKD among HIV-infected patients was higher than expected and reported by other authors. The only factors analysed that appeared to affect the presence of CKD were co-infection with HCV and exposure to lamivudine. Consequently, patients in treatment with lamivudine must be monitored and dose adjustments made. In our study, the exposure to TFV seems not to affect the prevalence. In spite of that it should be used cautiously because of its known nephrotoxicity.